THE PROTOTYPE OF A MAGNETOHYDRODINAMIC PROPULSION BOAT - ALFA FITHRIYAH (NIM. 90213011), AULIA
Magnetohydrodinamic (MHD) Propulsion Boat is one means of transportation applying electricity and magnetism. The boat uses electric field and magnetic field to accelerate and direct the ions in sea water so that the resulting propulsive force to move the boat. In this study, a prototype of magnetohydrodinamic propulsion boat has been made using a pair electrode of different materials, i.e. copper and zinc. Therefore, there is a potential difference between electrodes that generate electric field. Magnetic field is generated from two permanent bar magnets of NdFeB with grade N38. A propulsion unit is arranged from a pair of electrodes and two permanent bar magnets. The boat performance was tried using one propulsion unit and the boat moved with average speed of 0.12 cm/s. This speed is relatively low but it can be increased by adding another propulsion unit or connecting the electrode to a battery. Adding one propulsion unit can increase the boat’s speed by 0.10 cm/s and connecting the electrode to a 9-volt battery can increase the boat’s speed by 0.09 cm/s.